Peran Pengembangan Karir terhadap Kinerja Pegawai Dinas Kelautan dan Perikanan, Provinsi Sumatera Selatan - Muslimin, Boby (Jurnal Ilmu Manajemen, 2014)
Successful of an organization is determined by ability to adapt changes in the strategic environment to achieve good governance in government. The regulation of South Sumatra Provience No. 8 of 2008 about changes in the structure organization (resize) of Marine and Fisheries Agency of South Sumatra Province (DKP) that impact on Career Development (X) and performance (Y). The research was done in 6 months at DKP office, located at Jalan Pangeran Ayin , Jakabaring Palembang, starting from February-December 2013. The method is done by collecting secondary data and primary data in the form of questionnaires a total of 90 respondents to the census sampling, using multiple regression analysis and to see the effect of the variables and validating hypothesis. The result showed that the variables X significant effect on Y and X have a dominant influence on the performance of Y. employee performance is influenced by career development, which is used for policy in career opportunities.